Determinan kinerja keuangan dan good corporate governance terhadap financial distress model Altman - Mia Laksmiwati; Agoestina Mappadang; M. Ridwan Maulana (LPMP Imperium, 2022)
The purpose of this study is to analyze the effect of financial performance (Return On Assets, Current Ratio, Debt to Asset Ratio, Total Asset Turnover) and Good Corporate Governance as measured by Institutional Ownership, Managerial Ownership, Independent Commissioner, Audit Committee on Financial Distress against LQ index companies. – 45 for the period 2016 – 2020. For sampling using the purposive sampling method. This study takes a population of companies that go public on the Stock Exchange on the LG-45 Index and the sample results are 23 companies. Data analysis used multiple linear regression with SPSS ver. 25. This study shows that the results of financial performance (ROA, CR, DAR) and Good Corporate Governance which include Institutional Ownership, Management Ownership are significant to Financial Distress while TATO, Independent Commissioner, and Audit Committee are not significant to Financial Distress.